PENETAPAN STANDARDISASI HARGA OLEH ASOSIASI PELAKU USAHA (TRADE ASSOCIATION) DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA DI INDONESIA - Asi Islami, Trinah (Irtifaq, 2019)
The business associations set the standardization of prices of goods or services as a guide that must be obeyed by all members.. The existence of associations of business actors is often used as a container by business actors to cover up all their actions which incidentally indicates that monopolistic practices and unfair business competition are indicated. Basically, Law Number 5 Year 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition (hereinafter referred to as the Business Competition Law) has not explicitly and specifically regulated related sanctions for business associations of monopolistic practices and unfair business competition. The existence of the standardization of prices made and formed by the head of the association of business actors is a gap for business actors who are veiled in monopolistic practices and unfair business competition as prohibited by statutory regulations. Proof related to the determination of price standardization must be assessed using the per se illegal approach and the rule of reason and economic approach to find out whether there is an agreement on pricing and cartels or not. Keywords: Determination of Price Standardization, Cartel, Per se Illegal and Rule of Reason